OPTIMALISASI WAKTU ALIR TERHADAP ADSORPSI HIBRID SILIKA KITOSAN PADA SIMULTAN ION LOGAM Ni (II) DAN Cd (II) DENGAN METODE EKSTRAKSI FASE PADAT (EFP) - Simatupang, Lisnawati; Dewi, Ratna Sari; Samosir, Sri Rezeki (JURNAL PENELITIAN SAINTIKA, 2014)
Preparation of hybrid silica chitosan adsorben and used toadsorb heavy metals Ni(II), Cd(II) have been done. The research aims tofind out effeciency and selectivity of the hybrid silica chitosan to adsorbsheavy metals Ni(II) and Cd(II) using solid phase extraction method. Silica used is rice husk ash while chitosan used material is essentialy the shrimp shell. Previous research data shows that the optimum hybrid silica chitosan ratio is 20:4% ( 20 mL of sodium silicate solution : 0.4g chitosan in 10 mL of acetate 2%) with surface area of 189.405 m²/g. To determine the level of effectiveness and selectivity of adsorben was carried out on the variation of flow time (20,40,60,80,100) minutes. Result showed that the amount of metals ions tend to increased the following increase the flow time. The optimum condition at the time of 60 minutes, after wich the amount of metals ion adsorbs decreased. At the flow time of 60 minutes the amount of metal adsorbs for Ni(II) 58.1755 mg/L, Cd(II) 49.7392 mg/L . Solid phase extraction (SPE) method using hybrid silica more effective in adsorb chitosan adsorb was metal Ni(II) compared metal Cd(II) by order of the strenght of adsorptions Ni(II) > Cd(II)